Antibacterial effectiveness of peracetic acid and conventional endodontic irrigants - Guerreiro-Tanomaru,Juliane Maria (2011)
This study evaluated the in vitro antibacterial activity of conventional and experimental endodontic irrigants against Enterococcus faecalis. The following substances were evaluated by direct contact test: 2.5% sodium hypochlorite (NaOCl); 2% chlorhexidine (CHX); 1% peracetic acid. After different contact periods (30 s, 1, 3, and 10 min), a neutralizing agent was applied. Serial 10-fold dilutions were prepared and plated onto tryptic soy agar (TSA) and the number of colony-forming units per milliliter (CFU/mL) was determined. Sterile saline was used as a negative control. Both 2.5% NaOCl and 2% CHX eliminated E. faecalis after 30 s of contact. Peracetic acid reduced the bacterial counts by 86% after 3 min and completely eliminated E. faecalis after 10 min. These results allow us to conclude that 1% peracetic acid is effective against E. faecalis, despite its slower action compared with 2.5% NaOCl and 2% CHX.